استخدام محاسبة القيمة العادلة كأساس للقياس المحاسبي في الجزائر. - بن زاف, لبنى (جامعة الوادي - University of Eloued, 2020)
يهدف هذا البحث الى تطبيق نموذج القيمة العادلة كاساس للقياس المحاسبي وذلك بالتطرق الى اهم مفاهيم القيمة العادلة واهم ما توفره من طرق جديدة وملائمة للقياس المحاسبي،الذي يعتبر من الوظائف الاساسية للمحاسبة. من أهم النتائج المتحصل عليها صعوبة تطبيق مفهوم القيمة العادلة وهذا راجع إلى حداثة القيمة العادلة في البيئة المحاسبية الجزائريةـ،والى نقص وعي واهتمام المجتمع المحاسبي الجزائري بالمعايير المحاسبية الدولية،إضافة إلى ذلك عدم توفر أسواق مالية نشطة في الجزائر،فتطبيق نموذج القيمة العادلة كاساس للقياس المحاسبي يحقق خصائص نوعية للمعلومات المالية لتتمتع بالملائمة والموثوقية،وذلك لاتخاذ قرارات اقتصادية رشيدة. This research aims to apply the fair value model as a basis for accounting measurement by examining the most important concepts of fair value and the most important new and appropriate methods available for accounting measurement, which is considered one of the basic functions of accounting. One of the most important results obtained is the difficulty in applying the concept of fair value, and this is due to the novelty of fair value in the Algerian accounting environment, and to the lack of awareness and interest of the Algerian accounting community in international accounting standards, in addition to the lack of active financial markets in Algeria, so applying the fair value model as a basis for accounting measurement Achieves qualitative characteristics of financial information for convenience and reliability, in order to make rational economic decisions.
Keywords: القيمة العادلة،محاسبة القيمة العادلة ،القياس المحاسبي،النظام المحاسبي المالي،المعايير المحاسبية الدولية.